2007
DOI: 10.1002/app.26277
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and morphological properties of organic–inorganic, hybrid, clay‐filled, and cyanate ester/siloxane toughened epoxy nanocomposites

Abstract: Organic-inorganic hybrids involving cyanate ester and hydroxyl-terminated polydimethylsiloxane (HTPDMS) modified diglycidyl ether of bisphenol A (DGEBA; epoxy resin) filled with organomodified clay [montmorillonite (MMT)] nanocomposites were prepared via in situ polymerization and compared with unfilled-clay macrocomposites. The epoxy-organomodified MMT clay nanocomposites were prepared by the homogeneous dispersion of various percentages (1-5%), and the resulting homogeneous epoxy/clay hybrids were modified w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 39 publications
1
26
0
Order By: Relevance
“…When the modifier content increased to 8 wt% and 10 wt%, modified polysiloxanes aggregation happened in the modified epoxy resins, the size of second phase is so big that it may seriously affect the crosslinking density of the epoxy networks. The improvement in the impact strength is observed with the incorporation of both FPMS and EMPP, and this may be due to high-energy absorption, and resilient behavior of the flexible siloxane molecule, 30 as well as the defects and the lower crosslinking density of the network caused by the incorporating polysiloxanes.…”
Section: Resultsmentioning
confidence: 96%
“…When the modifier content increased to 8 wt% and 10 wt%, modified polysiloxanes aggregation happened in the modified epoxy resins, the size of second phase is so big that it may seriously affect the crosslinking density of the epoxy networks. The improvement in the impact strength is observed with the incorporation of both FPMS and EMPP, and this may be due to high-energy absorption, and resilient behavior of the flexible siloxane molecule, 30 as well as the defects and the lower crosslinking density of the network caused by the incorporating polysiloxanes.…”
Section: Resultsmentioning
confidence: 96%
“…Impact strength and K IC values of modified epoxies first increased with the increase in HEPSO2 content before 4 phr, which may be due to high-energy absorption, and resilient behavior of the flexible siloxane molecule, 34 as well as the defects and the lower crosslinking density of the network caused by the incorporating polysiloxanes. When the modifier content increased to 8 wt% and 12 wt%, the dispersed polysiloxane particles were so many that the particles seem to be contacted each other, as shown in Figure 5(c) and 5(d) (above), which might affect the crosslinking structure of the epoxy networks, and consequently the lower impact strength and K IC values.…”
Section: Resultsmentioning
confidence: 98%
“…Wooster et al [17] found that the crack resistance of the cyanate ester is improved by 80% by the addition of 4 wt% nanoclay without a sacrifice of flexural strength. Others have shown that the incorporation of nanoclay has similar enhancement on mechanical properties, toughness, and thermal properties of cyanate ester modified epoxy resin or cyanate/epoxy blends [18][19][20][21].…”
Section: Cyanate Ester-clay Nanocompositesmentioning
confidence: 99%
“…The gaps between rollers of the three-roll mill (Exakt 80E) used in this study were electronically adjustable [20]. Figure 3.17 shows pictures of the three-roll mill and how it works.…”
Section: Three-roll Millmentioning
confidence: 99%
See 1 more Smart Citation